Upaya Guru Pendidikan Kewarganegaraan dalam Menumbuhkan Budi Pekerti Siswa Melalui Gerakan Literasi Sekolah (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to describe the efforts of Civic Education teachers in fostering students' character through the implementation of the School Literacy Movement (GLS) at SMP Negeri 5 Ulunoyo. This research used a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results showed that Civics teachers have implemented various strategies, such as integrating moral values into learning materials, utilizing national-themed readings, getting students used to reading inspirational quotes, and providing literative assignments that emphasize ethical values and diversity. Teachers also guide students to reflect on Pancasila values through literacy activities. The obstacles faced include students' low interest in reading, limited character-oriented reading materials, lack of literacy facilities, limited Civics learning time, and lack of support from the family environment. To overcome these obstacles, teachers increase learning creativity by linking Civics material to inspirational stories and contextualized reflective tasks. The findings confirm the importance of integrative and innovative strategies in strengthening students' character through school literacy supported by adequate facilities